2013
DOI: 10.3109/14767058.2013.858685
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric manifestations of latent toxoplasmosis on mothers and their offspring

Abstract: Toxoplasmosis is one of the most common parasitic diseases worldwide. It is estimated that approximately one-third of the world's population is latently infected. Infection generally occurs via oral the route and maternal transmission. Damage of the central nervous system is one of the most serious consequences of congenital toxoplasmosis. Moreover, recent investigations proposed that acute and sub-acute congenital toxoplasmosis as well as latent toxoplasmosis during pregnancy; play various roles in the etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 99 publications
0
24
0
Order By: Relevance
“…Approximately one third of the world population is infected with T. gondii [CDC, ]. The parasite is primarily transmitted via food (undercooked meat), contaminated water, and cat waste [Abdoli et al, ; CDC, ]. Direct transmission of the parasitic infection in an adult or child most often causes no symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one third of the world population is infected with T. gondii [CDC, ]. The parasite is primarily transmitted via food (undercooked meat), contaminated water, and cat waste [Abdoli et al, ; CDC, ]. Direct transmission of the parasitic infection in an adult or child most often causes no symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, however, only a few studies have documented cognitive deficits in offspring following perinatal exposure to T. gondii (Brown et al, 2009; Mwaniki et al, 2012). A recent review, which included studies of latent maternal T. gondii exposure and offspring cognition and development, suggested that T. gondii’ s effect on dopamine systems in offspring may explain why offspring had delayed motor development, an increased prevalence of mental retardation and cognitive delays as well as increased risks of some neuropsychiatric illnesses (Abdoli et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Although it is estimated between 25 and 30% of the world’s human population is infected by T. gondii , and the most common form of infection is latent (asymptomatic) (Dalimi and Abdoli, 2012; Robert-Gangneux and Dardé, 2012). On the other hand, latent toxoplasmosis can induce different hormonal and behavioral alterations in humans and rodents (Flegr, 2013a,b) and involved in the etiology of various psychotic disorders (Dalimi and Abdoli, 2012; Flegr, 2013a; Abdoli et al, 2014). Different studies reported an increased concentration of testosterone in men with latent toxoplasmosis compared to the testosterone in Toxoplasma -negative individuals (Flegr et al, 2008a,b; Shirbazou et al, 2011; Zghair et al, 2014).…”
Section: Latent Toxoplasmosis Influence Testosterone Productionmentioning
confidence: 99%